Análisis de los determinantes del crecimiento económico del Ecuador en el periodo 1965 a 2006. - Granda Encarnación, Carmen Esperanza (2012)
The purpose of this study was to perform an approximation of the determinants of economic growth in Ecuador with data for the period 1965-2006, using four regressions were estimated ordinary least squares method. It is important for policy makers, understand the determinants of economic growth that may influence its policies and accelerate the growth of the country. Generally assumed that the higher the growth, especially if higher than the increase in population, income levels of the population are also higher, thus, favors the demand and the economic system is energized. The results of the econometric estimates indicate that the main determinants of economic growth in Ecuador are: investment, life expectancy, price of a barrel of oil, government consumption expenditure, exports and inflation.Likewise, we can note that the results of this study are consistent with results found in similar studies.